Community-based prehabilitation before elective major surgery: the PREP-WELL quality improvement project. Issue 1 (24th March 2020) - Tew, Garry Alan; Bedford, Robin; Carr, Esther; Durrand, James William; Gray, Joanne; Hackett, Rhiannon; Lloyd, Scott; Peacock, Sarah; Taylor, Sarah; Yates, David; Danjoux, Gerard
Abstract : Optimising health and well-being before elective major surgery via prehabilitation initiatives is important for good postoperative outcomes. In a busy tertiary centre in North East England, the lack of a formal prehabilitation service meant that opportunities were being missed to optimise patients for surgery. This quality improvement project aimed to implement and evaluate a community-based prehabilitation service for people awaiting elective major surgery: PREP-WELL. A multidisciplinary, cross-sector team introduced PREP-WELL in January 2018. PREP-WELL provided comprehensive assessment and management of perioperative risk factors in the weeks before surgery. During a 12-month pilot, patients were referred from five surgical specialties at James Cook University Hospital. Data were collected on participant characteristics, behavioural and health outcomes, intervention acceptability and costs, and process-related factors. By December 2018, 159 referrals had been received, with 75 patients (47%) agreeing to participate. Most participants opted for a supervised programme (72%) and were awaiting vascular (43%) or orthopaedic (35%) surgery. Median programme duration was 8 weeks. The service was delivered as intended with participants providing positive feedback. Health-related quality of life (HRQoL; EuroQol 5D (EQ-5D) utility) and functional capacity (6 min walk distance) increased on average from service entry to exit, with mean (95% CI) changes of 0.108 (−0.023 to 0.240) and 35 m (−5 to 76 m), respectively. Further increases in EQ5D utility were observed at 3 months post surgery. Substantially more participants were achieving recommended physical activity levels at exit and 3 months post surgery compared with at entry. The mean cost of the intervention was £405 per patient; £52 per week. The service was successfully implemented within existing preoperative pathways. Most participants were very satisfied and improved their risk profile preoperatively. Funding has been obtained to support service development and expansion for at least 2 more years. During this period, alternative pathways will be developed to facilitate wider access and greater uptake.